Personal Finance in Today’s Complex World - eBooks and textbooks from bookboon.com - Fredricks, Thomas (bookboon.com, 2016)
This book is written to help someone negotiate the often tricky world of personal finance. Understanding savings and investments – for the long and short term – need not be a big mystery; nor should it be something the average person is afraid to look into. All of the options open involve choices. It is the author’s hope to make these choices clearer and easier, and to help promote a safe return on one’s investments.